The economic situation and social interactions of prisoners’ families - Dzierzyńska-Breś, Sonia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This article shows the current state of knowledge about: the economic situation and social interactions of families of prisoners. An in-depth analysis of own research, as well as those presented so far in Polish and foreign literature, has allowed to distinguish three types of social situations of families of prisoners, with particular emphasis on their economic situation and social interactions, namely; (1) the social situation of a family supporting the resocialization of the prisoner, (2) the social situation of a prisoner’s family, which is in opposition to the process of resocialization, (3) the social situation of a family focused on the reconstruction of its own social environment.